algebra

posted by .

am I right?
1. Simplify radical expression
sqrt 50
5 sqrt ^2***
2 sqrt ^5
5 sqrt ^10
5
2. Simplify the radical expression sqrt 56x^2
28x
2x sqrt 14***
2x sqrt 7
sqrt 14x2

3. Simplify the radical expression.
sqrt 490y^5w^6
2 sqrt 135y^2
2y sqrt 135***
27 sqrt 15y^2
27y sqrt 15

4. Simplify the radical expression.
sqrt15y multiplied by 3 sqrt 81y
2 sqrt 135y^2
2y sqrt 135***
27 sqrt 15y^2
27y sqrt 15

5. Simplify the radical expression.
sqrt 20x^13y^5/5xy^7
sqrt 4x^12/y^2
2x^6/y
2 sqrt x^12/y^2
2x^6y***

6. Simplify the radical expression.
sqrt 5+6 sqrt 5
5 sqrt 5
7 sqrt 10***
7 sqrt 5
5 sqrt 10

7. Simplify the radical expression.
5 sqrt 7 + 3 sqrt 175
7 sqrt 182
15 sqrt 14
5 sqrt 175***
15 sqrt 7

8. Simplify the radical expression.
(3+sqrt6)(3-sqrt6)
-27
3
9+6sqrt6
15+6sqrt6***

9. What is the domain function? y=sqrt3x+3
x<=-1
x>1
x>=-1***
x<1

10.Simplify the radical expression by rationalizing the denominator.
3 sqrt 160/sqrt 1350x***
2 sqrt 15x/15x
3 sqrt 160/1359x
4sqrt15x/15x
4/sqrt45x

  • algebra -

    #1 and #2 are correct

    #3
    √(490y^5w^6)
    = √49√10 (y^2√y)(w^3)
    = 7√10 y^2w^3 √y <--- not one of the choices

    #4
    (√(15y))(3√(81y))
    = √15√y (27√y)
    = 27y√15

    #5 can't tell where the square root ends without brackets

    #6
    1 apple + 6 apples = 7apples
    1dollar + 6 dollars = 7 dollars
    1√5+ 6√5 = 7√5

    #7
    5 √7 + 3√175
    = 5√7 + 3√25√7
    = 5√7+15√7
    = 20√7 <--- not one of the choices! but correct answer

    #8
    (3+sqrt6)(3-sqrt6)
    difference of square pattern
    = 9 - 6
    = 3

    #9
    y=√3x+3
    depends if brackets are needed

    the way you typed it, domain is x ≥ 0
    if you meant:
    y = √(3x+3) , then 3x+3 ≥ 0 ----> x ≥ -1

    #10
    3√160/√(1350x) ,
    = 12√10 / (√10√135√x)
    = 12/√(135x) * √(135x)/√(135x)
    = 12√(135x)/135x

    3 sqrt 160/1359x would have been a correct expression if it had brackets such as:
    3√(160/(1359x) ) , but then it would not have been rationalized.
    None of the other choices are correct.

    You got 2 right out of 10
    guessing would have given you (1/4)(10) or 2.5 correct.
    You did worse than just plain guessing.

    Where did you get these questions??

  • algebra -

    I noticed I completely switched up choices of some answers due to the fact I had to write all these answers down and it my mind felt cluttered. thanks for the reply though, would you like if I were to rewrite them all or something?

  • algebra -

    actually nevermind I finished the questions rn my answers are correct thank you

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    how would you simplify this equation: y = (x+3)/[(4-sqrt(16+h))] please help me! you have three variables. I am not certain "simplify" is an appropriate term here. ohhhh it was my mistake. I meant: y = h/[(4-sqrt(16+h))] y = h/[(4-sqrt(16+h))] …
  2. math calculus please help!

    l = lim as x approaches 0 of x/(the square root of (1+x) - the square root of (1-x) decide whether: l=-1 or l=0 or l=1 Let me make sure I understand the question. Do we have lim x->0 x/[sqrt(1+x) - sqrt(1-x)] ?
  3. math help

    15sqrt8x^15/5sqrt2x^4 remember that sqrt(a)/sqrt(b) = sqrt(a/b) simplify the inside. also notice that sqrt(x^11) = sqrt(x^10) * sqrt(x) = x^5 * sqrt(x)
  4. math,algebra,help

    Directions are simplify by combining like terms. x radiacal 18 -3 radical 8x^2 can someone show me how to do these types of problems. thanks I cant determine the second term. For the first, I think you meant x sqrt(18) which reduces …
  5. Math

    How do you find a square root of a number that's not a perfect square?
  6. algebra,math,help

    Use Property 2 to simplify each of the following radical expressions. sqrt (10)/ sqrt(49) My answer: sqrt (10) / (7) THis next one i need help: Use the properties for radicals to simplify each of the following expressions. Assume that …
  7. Math Help please!!

    Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine …
  8. algebra

    simplify: square root of 5 + square root of 20 - square root of 27 + square root of 147. simplify: 6/4square root of 2 sqrt 5 + sqrt 20 - sqrt 27 + sqrt 147 = sqrt 5 + sqrt (4*5) - sqrt (3*9) + sqrt (49*3) = 3 sqrt 5 - 3 sqrt 3 + 7 …
  9. algebra

    simplify the following radical expression: 3 sqrt () -216x^2/x^2 a) sqrt() -6x b)-6 c)-6 sqrt()x d) 6 sqrt()-x
  10. Algebra

    Evaluate sqrt7x (sqrt x-7 sqrt7) Show your work. sqrt(7)*sqrt(x)-sqrt(7)*7*sqrt(7) sqrt(7*x)-7*sqrt(7*7) sqrt(7x)-7*sqrt(7^2) x*sqrt 7x-49*x ^^^ would this be my final answer?

More Similar Questions